Integrated management for the environment care and conservation project’s results - Alina Arocha Arzuaga; Virginia Cano Reyes; Roberto Felipe Nicot Cos; Ada Legna Montoya Lage (Medisur)
Foundation: caring for the environment, the survival of the human species and other species that populate the planet is of great importance, however, there is a few dissemination of the research related to the topic’s results. Objective: evaluate the preliminary results of a research project on environmental care. Methods: a qualitative study was carried out from January 2021 to July 2023. The primary information was obtained through the semiannual report model of the Integrated Management research project for the care and conservation of the environment; and by evaluating achievement with its schedule. Results: from the project, 9 papers were presented at events, which were of the scientific impact. In the social order, the contribution to the training of human resources was highlighted through the execution of 6 completion projects in the specialty of Comprehensive General Stomatology. As an environmental impact, a diagnosis of the Faculty property technical state and structural behavior of multi-dangers was developed, by virtue of which an environmental management strategy was designed and approved. Conclusions: the research project constitutes a strength that is evident in the results achieved. Despite the transformations carried out, management still needs to be improved to comply with the proposed schedule for the benefit of the environment and the health of the community.